Resonant Tunneling Spectroscopy to Probe the Giant Stark Effect in Atomically Thin Materials. Issue 12 (6th February 2020) - Zheng, Shoujun; Jo, Sanghyun; Kang, Kyungrok; Sun, Linfeng; Zhao, Mali; Watanabe, Kenji; Taniguchi, Takashi; Moon, Pilkyung; Myoung, Nojoon; Yang, Heejun
Abstract: Each atomic layer in van der Waals heterostructures possesses a distinct electronic band structure that can be manipulated for unique device operations. In the precise device architecture, the subtle but critical band splits by the giant Stark effect between atomic layers, varied by the momentum of electrons and external electric fields in device operation, has not yet been demonstrated or applied to design original devices with the full potential of atomically thin materials. Here, resonant tunneling spectroscopy based on the negligible quantum capacitance of 2D semiconductors in resonant tunneling transistors is reported. The bandgaps and sub‐band structures of various channel materials could be demonstrated by the new conceptual spectroscopy at the device scale without debatable quasiparticle effects. Moreover, the band splits by the giant Stark effect in the channel materials could be probed, overcoming the limitations of conventional optical, photoemission, and tunneling spectroscopy. The resonant tunneling spectroscopy reveals essential and practical information for novel device applications. Abstract : The giant Stark effect, exhibited by the energy splits of the unoccupied conduction band, is clearly demonstrated by resonant tunneling spectroscopy at the device scale. Furthermore, pristine bandgaps of monolayer MoS2 and WSe2 can be precisely measured by the negative differential resistance peak position.